2014
DOI: 10.4103/0253-7613.125192
|View full text |Cite
|
Sign up to set email alerts
|

A study of agreement between the Naranjo algorithm and WHO-UMC criteria for causality assessment of adverse drug reactions

Abstract: Objectives:Reliability and usefulness of various adverse drug reaction (ADR) causality assessment scales have not been fully explored. There is no universally accepted method for causality grading of ADRs. In the present study we assessed agreement between the two widely used causality assessment scales, that is, the World Health Organization-Uppsala Monitoring Center (WHO-UMC) criteria and the Naranjo algorithm.Materials and Methods:The same observer assessed all ADRs (n = 913) collected between January 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 15 publications
1
44
1
1
Order By: Relevance
“…Causality assessment aid regulatory authorities in evaluating ADRs and risk-benefit decisions about medicines. 10,11 Causality assessment algorithms are organised frameworks that help in objective decision making on causality. 12 Causality assessment should be recommended and performed widely once ADR monitoring is intensified in all health care institute by educating and motivating healthcare providers to report ADRs.…”
Section: Discussionmentioning
confidence: 99%
“…Causality assessment aid regulatory authorities in evaluating ADRs and risk-benefit decisions about medicines. 10,11 Causality assessment algorithms are organised frameworks that help in objective decision making on causality. 12 Causality assessment should be recommended and performed widely once ADR monitoring is intensified in all health care institute by educating and motivating healthcare providers to report ADRs.…”
Section: Discussionmentioning
confidence: 99%
“…II), were similar for the both D-ADRs and CM-ADRs. However, a previous study reported poor agreement between the Naranjo algorithm and WHO-UMC criteria [ 32 ]. In another study, “probable” or “certain” ADRs were scored more often when using the Korean algorithm (ver.…”
Section: Discussionmentioning
confidence: 99%
“…Many causality scoring systems have been used for evaluation of adverse drug reaction. We used Naranjo score and WHO-UMC in our patients and it was “probable” and “certain” ADR according to these categories, respectively [ 18 ].…”
Section: Discussionmentioning
confidence: 99%